Coherent perfect absorption and reflection in slow-light waveguides - Gutman, Nadav. (2014)
We identify a family of unusual slow-light modes occurring in lossy multimode grating waveguides, for which either the forward or backward mode components, or both, are degenerate. In the fully degenerate case, the response can be modulated between coherent perfect absorption (zero reflection) and perfect reflection by varying the wave amplitudes in a uniform input waveguide. The perfectly absorbed wave has anomalously short absorption length, scaling as the inverse one-third power of the absorptivity.